Thickness Distributions of Mold Flux Film and Air Gap in Billet Ultra-High Speed Continuous Casting Mold Through Multiphysics Modeling - Xu, Pei; Wang, Sijie; Zhou, Yongzhi; Chen, Dengfu; Long, Mujun; Duan, Huamei (Frontiers in Materials, 2022)
The thicknesses of mold flux film and air gap are significant factors that affect the high-efficiency heat transfer, the strand lubrication and mold taper design of billet ultra-high speed continuous casting mold. Therefore, this paper established the three-dimensional fluid flow, heat transfer and solidification model, interfacial heat transfer model and two-dimensional stress-strain model to conduct multiphysics modeling. Thereby the thickness distributions of liquid slag, solid slag and air gap in the ultra-high speed billet continuous casting mold were obtained, and analyzing the effects of melting temperature of mold flux and mold taper. The results indicate that the thicknesses of liquid slag and solid slag increase and decrease respectively along the casting direction, and air gap mainly concentrates near the mold corner. The maximum thicknesses of liquid slag, air gap and solid slag at the mold outlet are respectively 0.18 mm at the center of the strand surface (x=0 mm), 0.28 mm at the strand corner (x=80 mm) and 0.67 mm at x=74 mm. The lower melting temperature of mold flux, the greater the liquid slag thicknesses and ascend from 0.14 mm to 0.18 mm, and conversely the maximum air gap thicknesses descend from 0.31 mm to 0.28 mm and existing ranges also get smaller, which is more favorable for the strand lubrication. To eliminate the air gap, the appropriate linear mold taper is 0.45% m-1 at the 6.5 m/min in casting speed.